1997
DOI: 10.1053/jhep.1997.v26.ajhep0261361
|View full text |Cite
|
Sign up to set email alerts
|

TIPSS trials: Design determines outcome

Abstract: survival rates for shunted and endoscopically treated patients Methods: Sixty-three consecutive cirrhotic patients with a of 90% and 89%, and 2-year survival rates of 79% and 82%, hemorrhage from esophageal varices were included. Thirtyrespectively. The incidence of clinically significant hepatic two patients were randomly allocated to ES and 31 to TIPS encephalopathy after 1 year was higher in the shunt group groups. Results: One patient in each group died before the (36% vs 18%, P Å 0.011). Interpretation: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Considering the high mortality associated with uncontrolled variceal bleeding, an effective TIPS So far, three published uncontrolled trials report on TIPS placement in the setting of uncontrolled variceal rescue obviously improves the overall survival data -analyzed on an intention-to-treat basis -in favor of the bleeding after one to two endoscopic interventions [9][10][11]. One study compared the outcome of emergency TIPS endoscopy cohort [17]. All authors reported TIPS as an effective rescue measure without giving separated early with an historic control group using esophageal transection as salvage treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high mortality associated with uncontrolled variceal bleeding, an effective TIPS So far, three published uncontrolled trials report on TIPS placement in the setting of uncontrolled variceal rescue obviously improves the overall survival data -analyzed on an intention-to-treat basis -in favor of the bleeding after one to two endoscopic interventions [9][10][11]. One study compared the outcome of emergency TIPS endoscopy cohort [17]. All authors reported TIPS as an effective rescue measure without giving separated early with an historic control group using esophageal transection as salvage treatment [10].…”
Section: Introductionmentioning
confidence: 99%